Studi Kerapatan Ekosistem Mangrove Desa Sungai Cemara Kab Tanjung Jabung Timur Provinsi Jambi - Mandala, Bakti; Purwati, Betty; Pandu Winata, Riki (Journal of Tropical Silviculture, 2025)
Sungai Cemara Village, located in Tanjung Jabung Timur Regency, Jambi Province, is part of the East Coast Mangrove Forest Nature Reserve and directly borders Berbak Sembilang National Park. This area encompasses approximately 300 hectares of mangrove ecosystems that play a crucial role in coastal protection and serve as habitat for various wildlife species, including migratory birds and the Sumatran tiger. This study aims to analyze the vegetation structure and habitat characteristics of the mangrove ecosystem in the region. The research employed a vegetation survey method across five transects comprising a total of 100 plots, covering three growth stages: seedlings, saplings, and mature trees. The results showed that Avicennia sp. was the dominant species with the highest Important Value Index (IVI) across all growth stages—1.31% in seedlings, 1.34% in saplings, and 1.48% in mature trees. Environmental parameters indicated favorable conditions for mangrove growth, with temperatures ranging from 28–30°C, salinity between 23–25 ppt, soil and water pH values between 6 and 7, and predominantly muddy substrates. These findings suggest that the mangrove ecosystem in Sungai Cemara Village is in a good regenerative condition and holds strong potential for ecologically based conservation efforts.